The One Health Concept: Working on a more efficient healthcare system - VAN WILLIGEN, Gijsbert (One Health & Risk Management, 2023)
One Health Concept of the world Health Organisation is not a new concept, but it was somewhat neglected over the years. However, the concept is a very important one. It recognizes that human health, animal health and environmental health are interconnected instead of separate subjects. Furthermore it is very important for how we (should) look at human health care. Besides these 3 main fields also food safety is part of the One Health Concept. A lot of the yearly illnesses derive from contaminated food or are transmitted by food. Some even say that more than half of the illnesses in human originate from food sources. Examples from recent history that started from food are the Ebola outbreak in West Africa by bush meat and the the SARS-CoV-2 pandemic that probably started at a food market in Wuhang, although for the last is still no conclusive evidence. At the moment we treat patients in hospital that are ill as we did in the past and what we will keep on doing in the future. That is of course a good approach, but aren’t we treating symptoms of a much bigger problem? To my opinion we don’t tackle the actual source of the disease that mainly lies not in the patient itself but in his surrounding like the environment, life style, food safety (in the broadest sense of the word) or even the genetic composition of the patient. Sometimes, we even can’t treat patients anymore because of the antibiotic resistance of microorganisms that is derived from the animal industry to provide us with food products. With the strategy of the One Health Concept we can address and solve main causes of human diseases that lay outside of the health care system. It is an integrated approach in which experts from all fields that need to be involved will work together and find solutions for, not only human diseases, but also solutions for better food safety, animal health and environmental health including the climate changes we are suffering from right now. It is an integrated approach where no borders between all involved disciplines should be present and a new integrated way of thinking must be present. Main thing is that a lot of issues must be tackled and solved. Only with the integrated approach of the One Health Concept it should be feasible to reach the targets. However, for reaching the targets of the One Health Concept a lot of other people will be involved besides the experts. Without policy makers and politicians the One Health Concept will not work, because only with a global approach targets will be reached. Without the commitment of politicians from all countries problems will be tackled only locally, instead of the global approach needed for the One Health Concept. For the One Health Concept a platform where information can be shared. One example is the journal One Health & Risk Management which regularly pays attention to subjects of the One Health Concept.